FUNCTIONALITY OF MOODLE E-AVIATION METEOROLOGY IN AVIATION POLYTECHNIC OF SURABAYA - Rahmawan, Andi; Rochmawati, Laila; Hadi Rantelinggi, Parma; Putra, Iwansyah (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
In learning Aviation Meteorology e-modules that specifically study it have not been facilitated in the Learning Management System of Surabaya Aviation Polytechnic. This research aims to develop a learning module for Aviation Meteorology. This Final Project uses a research method, namely Research and Development (R&D) by conducting data collection techniques in the form of interviews and questionnaires. From this study, it was found that the results of the Material Expert Validation Test obtained the category "Valid" and "Understandable". Then the Media Validation Test obtained the "Valid" and "Understandable" categories, and the Product Trial to the cadets obtained a correlation coefficient score of 0.85 in the "Very Strong" category because the results produced did not produce a minus score, meaning that the relationship was positive and the Aviation Meteorology E-Module was effective in helping cadets understand the Aviation Meteorology course